2015
DOI: 10.1161/strokeaha.114.008088
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Postinfarct Myelin-Associated Glycoprotein Antibody Treatment on Motor Recovery and Motor Map Plasticity in Squirrel Monkeys

Abstract: Background and Purpose-New insights into the brain's ability to reorganize after injury are beginning to suggest novel restorative therapy targets. Potential therapies include pharmacological agents designed to promote axonal growth. The purpose of this study was to test the efficacy of one such drug, GSK249320, a monoclonal antibody that blocks the axon outgrowth inhibition molecule, myelin-associated glycoprotein, to facilitate recovery of motor skills in a nonhuman primate model of ischemic cortical damage.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 23 publications
(19 reference statements)
0
15
0
2
Order By: Relevance
“…An anti-NogoA antibody chimera has been tested in human spinal cord injury, and has a wealth of evidence in pre-clinical stroke models (Lindau et al, ’14; Wahl et al, 2014). An anti-myelin associated glycoprotein antibody chimera also has been taken into Phase 1 studies in humans (Cramer et al, 2013) and has shown promise in pre-clinical models (Barbay et al, 2015). An important question of these kinds of biologics is that, as large proteins, do they penetrate the blood brain barrier to enter the post-stroke brain in sufficient concentration?…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…An anti-NogoA antibody chimera has been tested in human spinal cord injury, and has a wealth of evidence in pre-clinical stroke models (Lindau et al, ’14; Wahl et al, 2014). An anti-myelin associated glycoprotein antibody chimera also has been taken into Phase 1 studies in humans (Cramer et al, 2013) and has shown promise in pre-clinical models (Barbay et al, 2015). An important question of these kinds of biologics is that, as large proteins, do they penetrate the blood brain barrier to enter the post-stroke brain in sufficient concentration?…”
Section: Future Directionsmentioning
confidence: 99%
“…Much research needs to be done to define timing of these two approaches, and the timing might differ according to the specific mechanism of action of a candidate axonal sprouting therapy. For example, a therapy that stimulates a neuronal axonal growth program (Li et al 2015) might have a different optimal time window and interaction with neurorehabilitation than an anti-growth inhibitor approach (Overman et al, 2012; Wahl et al, 2014; Barbay et al, 2015). …”
Section: Future Directionsmentioning
confidence: 99%
“…An antimyelin-associated glycoprotein antibody has recently been tested in a phase I trial in stroke [115]. The data from preclinical studies of axonal sprouting would suggest that this will not be effective, and preclinical models show that it is only modestly successful in either preventing the initial dysfunction after stroke or producing limited behavioral recovery [116]. Other molecular pathways for axonal sprouting, either induced in peri-infarct neurons or contralateral neurons [98], indicate promising targets for neural repair such as ephrin-A5, GDF10, and the use of the small molecule inosine [36,69,98,113].…”
Section: Potential Neural Repair Therapiesmentioning
confidence: 99%
“…Гиперактивация Rho-ROCK-сигнального пути под воздействием миелинассоциированных ингибиторов влияет и на восстановление после инсульта [65,66]. Миелинассоциированные протеины -ингибиторы роста аксонов синтезируются также некоторыми субпопуляциями клеток сетчатки и оказывают влияние на восстановление после повреждений зрительных нервов [67].…”
Section: другие заболеванияunclassified
“…С целью возможного терапевтического влияния на рост и регенерацию аксонов изучали антагонисты к рецептору Nogo-66 (NgR1) [70], ингибитор гликозилирования хондроитинсульфатных протеогликанов PTPσ [53], моноклональные антитела против миелинассоциированных протеинов-ингибиторов аксонального роста. В недавнем исследовании [65] эффект моноклонального антитела GSK249320 против миелинассоциированного гликопротеина (MAG) показан на модели кортикального ишемического инсульта: у приматов, получавших GSK249320, к 16-му дню заболевания функциональное восстановление было достоверно лучше, чем в контрольной группе. Важно, что функциональное преимущество опытной группы было получено не за счет периинфарктной области и прилегающей премоторной зоны, что было продемонстрировано нейрофизиологическим -картированием двигательных зон (представительство вентральной премоторной зоны в экспериментальной группе было меньше, чем в контроле).…”
Section: ингибиторы Rhoa и другие потенциальные лекарственные средстваunclassified